2020
DOI: 10.3390/nu12103138
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Folate Supplementation on Homocysteine and Cognition in Patients with Folate Deficiency and Cognitive Impairment

Abstract: Although folate deficiency was reported to be associated with hyperhomocysteinemia, influence of folate supplementation on cognition remains controversial. Therefore, we explored the effects of folate supplementation on the cognition and Homocysteine (Hcy) level in relatively short periods in patients with folate deficiency and cognitive impairment. Enrolled 45 patients (mean age of 79.7 ± 7.9 years old) with folate deficiency (<3.6 ng/mL) with cognitive impairment underwent Mini-Mental State Examination (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 62 publications
(168 reference statements)
2
30
0
Order By: Relevance
“…Notably, an association between homocysteine metabolism, oxidative stress and immune activation has been proven [ 34 ]. Low folate levels were also found to be associated with lower baseline MMSE scores in previous research [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 63%
“…Notably, an association between homocysteine metabolism, oxidative stress and immune activation has been proven [ 34 ]. Low folate levels were also found to be associated with lower baseline MMSE scores in previous research [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 63%
“…Although this is a very small-scale study, a larger population-based study is needed to find any valid correlation between different B vitamins and hyperhomocysteinemia among AD and MCI patients. In patients with folate deficiency, cognitive impairment was ameliorated by folate supplementation for a short period [174]. Inflammation is one of the major factors that lead to progressive neurodegeneration in AD.…”
Section: Vitamins Based Clinical Studies In Alzheimer's Diseasementioning
confidence: 99%
“…Similar results were found by Yuka Hama et al, (2020) who administered folate in deficient patients. They found that reduced Hcy levels correlated with better scores in the mini-mental state examination (MMSE) [188].…”
Section: Vitamins (Deficit/supplement)mentioning
confidence: 99%